Pembekalan tentang Digital Marketing Strategy bagi Pengurus dan Anggota Dekopinda Jakarta Utara - Tony Sitinjak; Budi Berlinton Sitorus; Martha Ayerza Esra; Elis Sondang Dasawaty; Farida Komalasari (President University, 2021)
Currently mastery of digital marketing has become a must for business people. However, there arestill many parties who have not mastered it. In order to provide briefing and enrichment on digitalmarketing strategy, this community service activity (PKM) was carried out in collaboration withDekopinda - North Jakarta. Starting with the formulation of the problem, followed by the formulation ofthe material and the determination of the form of activity, this PKM was carried out on June 26, 2021using an online platform, because it took place in the midst of the Covid-19 Pandemic and theimplementation of the PPKM Mikro in DKI Jakarta. This activity was attended by 35 participants whoare the Managements and Members of Dekopinda – North Jakarta. The material presented includesthe understanding of digital marketing, digital marketing channels, internet marketing and its mainchannels, how to start digital marketing, strategies for choosing social media as a promotional tool,and how to choose a marketplace for beginners. After participating in this activity, participants feltgreat benefits and suggested similar activities with different topics. The proposed topics areleadership and identification of business opportunities during a pandemic.